Structural characterization of micro- and mesoporous carbon materials using in situ high pressure 129Xe NMR spectroscopy - Oschatz, Martin; Hoffmann, Herbert C.; Pallmann, Julia; Schaber, Jana; Borchardt, Lars; Nickel, Winfried; Senkovska, Irena; Rico-Frances, Soledad; Sivestre-Albero, Joaquin; Kaskel, Stefan; Brunner, Eike (Chemistry of Materials, 2014)
In situ high pressure 129Xe NMR spectroscopy in combination with volumetric adsorption measurements were used for the textural characterization of different carbon materials with well-defined porosity including microporous carbide-derived carbons, ordered mesoporous carbide-derived carbon, and ordered mesoporous CMK-3. Adsorption/desorption isotherms were measured also by NMR up to relative pressures close to p/p0 = 1 at 237 K. The 129Xe NMR chemical shift of xenon adsorbed in porous carbons is found to be correlated with the pore size in analogy to other materials such as zeolites. In addition, these measurements were performed loading the samples with n-nonane. Nonane molecules preferentially block the micropores. However, 129Xe NMR spectroscopy proves that the nonane also influences the mesopores, thus providing information about the pore system in hierarchically structured materials. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20